(untitled) (AYUSHDHARA, 2019)
Ayurveda is divided into eight branches for simplifying the understanding of the subjects by scholars. Agadatantra (Ayurvedic Toxicology) is one of the branch which deals with the study of signs and symptoms of Sthavara (animate) and Jangama (inanimate poisoning). Present study is an attempt to study the applied aspect of Raktamokshana in Vishachikitsa. Modern line of treatment for poisoning cases also consists of elimination of poisons through various means. Both general and particular stage wise (Vegas) signs and symptoms, is a special feature of Ayurveda diagnosis of poisoning cases. Vega is the ability of poison to invade the Dhatus quickly and consecutively. In this sense Raktamokshana is indicated in very first Vega. Hence it is the foremost therapy prescribed in Vishachikitsa. Materials and Methods: all the major classics of Ayurveda be reviewed to collect all the data related to Vishachikitsa and Raktamokshana, earlier published work on the topic. Discussion: Raktamokshana (bloodletting) is the easy and fastest way of removal of poison from the site of bite. Fast relief from the symptoms of poisoning is possible and is one of the important and foremost procedure in Jangamavisha (animate poisons). Sthaavaravisha (plant poison) Chikitsa and prime treatment in chronic cumulative poisonings like Dushivisha (combatant cumulative poison) and Garavisha (artificial cumulative poison). Raktamokshana is one of the principal Shodhana (detoxification) therapies in Ayurveda. Conclusion: Indications of Raktamokshana are widely indicated in most of the blood borne diseases, poisoning, and skin disorders.